1982
DOI: 10.1159/000128220
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Acute Ethanol Intoxication on Primary Haemostasis, Coagulation Factors and Fibrinolytic Activity

Abstract: The effect of ethanol intoxication on haemostasis was studied by transection of mesenteric microvessels and liver resection in the rat. Plasma concentrations of alcohol were within the range of those found in ethanol intoxication in man. Bleeding time and blood loss were increased 1 h after ethanol administration, regardless of the utilized technique. A significant positive correlation existed between bleeding time following liver resection and bleeding time after simultaneous transection of a mesenteric arter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
13
0

Year Published

1984
1984
2006
2006

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 11 publications
3
13
0
Order By: Relevance
“…Some studies have found an upregulation of tPA expression and a decrease in PAI-1 transcription, something that would explain the increased fibrinolytic activity [33][34][35][36]. However, there are also studies having found an acute inhibitory effect or no effect at all of ethanol on fibrinolysis [9][10][11]. We found a decrease in fibrinolytic activity in this study, a finding supporting van de Wiel et al who found similar results in their study [11].…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Some studies have found an upregulation of tPA expression and a decrease in PAI-1 transcription, something that would explain the increased fibrinolytic activity [33][34][35][36]. However, there are also studies having found an acute inhibitory effect or no effect at all of ethanol on fibrinolysis [9][10][11]. We found a decrease in fibrinolytic activity in this study, a finding supporting van de Wiel et al who found similar results in their study [11].…”
Section: Discussionsupporting
confidence: 89%
“…However, these studies have in general been performed on components of blood, rather than on whole blood, and the effects reported are not in agreement. Several studies have found an alcohol induced impairment of the primary hemostasis, whereas the humoral coagulation factors and the fibrinolytic system were unaffected [7][8][9]. El-Sayed et al [10] corroborated these results on the humoral coagulation factors and the fibrinolysis, but others have found an acute impairment of the fibrinolytic system by increased ethanol levels [11,12].…”
Section: Introductionmentioning
confidence: 98%
“…After midline laparotomy, the spleen was exposed and a pre-weighed aluminium cup was placed under the caudal pole. Approximately 0.01 g (1%) of the caudal splenic pole was resected in a standardized manner, according to Zoucas et al [28]. Bleeding time was equal to the time required for the formation of hemostafic a plug, which was recorded by observing the bleeding surface through a microscope at 10 x magnification.…”
Section: Determination Of Norepinephrine (Ne) Content In Splenic Tissuementioning
confidence: 99%
“…Standardized transection of mesenteric microvessels with a diameter of 250-300 gm was carried out as previously described [28]. Bleeding time and blood loss were recorded as described above.…”
Section: Determination Of Blood Loss and Bleeding Time After Mesentermentioning
confidence: 99%
“…Infusion of NE or 0.9% NaCl was per formed according to the experimental protocol, using a Harward pump. A standardized resection of the left anterior liver lobe was performed by means of a pair of scissors as described earlier [14], Two to three per cent of the total liver weight was excised. Bleeding time was registered by observing the traumatized sur face through an operating microscope.…”
Section: Methodsmentioning
confidence: 99%